2017
DOI: 10.1038/emm.2017.17
|View full text |Cite
|
Sign up to set email alerts
|

Progress of antibody-based inhibitors of the HGF–cMET axis in cancer therapy

Abstract: Dysregulated receptor tyrosine kinase signaling in human cancer cells leads to tumor progression, invasion and metastasis. The receptor tyrosine kinase cMET is frequently overexpressed in cancer tissue, and activation of cMET signaling is related to drug resistance and the processes of carcinogenesis, invasion and metastasis. For that reason, cMET and its ligand, hepatocyte growth factor (HGF), are considered prime targets for the development of anticancer drugs. At least eight anti-cMET and four anti-HGF anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 71 publications
(51 reference statements)
1
64
0
Order By: Relevance
“…Targeting the HGF-c-MET pathway has been approached for the treatment of a variety of solid tumours with deregulated c-MET 44. However, tyrosine kinase inhibitors (TKI) of c-MET, monoclonal antibodies or small molecules designed to block the HGF/c-MET interaction have proven insufficient 45.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting the HGF-c-MET pathway has been approached for the treatment of a variety of solid tumours with deregulated c-MET 44. However, tyrosine kinase inhibitors (TKI) of c-MET, monoclonal antibodies or small molecules designed to block the HGF/c-MET interaction have proven insufficient 45.…”
Section: Discussionmentioning
confidence: 99%
“…Their potential immunogenicity and high production costs are of particular concern for this modality. In addition, selective c‐met small‐molecule inhibitors have failed to gain approval due to adverse effects, dose‐limiting toxicities or acquired resistance; therefore, novel approaches that suppress HGF/c‐met signaling are needed . In the last decade, aptamers have emerged as attractive alternatives to antibodies and small molecules and have found use in diagnostic, therapeutic, imaging and targeting applications .…”
Section: Discussionmentioning
confidence: 99%
“…5 We evaluated the mRNA expression of c-met in two independent publicly available data sets and showed that c-met While multiple antibodies that target c-met or HGF are under preclinical and clinical development, none of them have shown significant clinical benefit to patients. 29 Their potential immunogenicity and high production costs are of particular concern for this modality.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant protein (truncated HGF, decoy c-Met) was not successful in clinical trials due to several factors, including short half-life and low target affinity limiting the intended efficacy [28]. Several HGF-neutralizing antibodies have been developed with two currently active in clinical trials [29]. However, the inhibitory targeting of c-Met by an antibody has been difficult since the bivalency of antibodies often induces receptor dimerization, which potentially causes cancer cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%